2009
DOI: 10.1007/s00415-009-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

A decision tool to support appropriate referral for deep brain stimulation in Parkinson’s disease

Abstract: The RAND/UCLA method proved to be useful in determining the appropriate criteria for DBS referral. Validity and applicability of the decision tool (accessible via http://test.stimulus-dbs.org) in clinical practice need to be further determined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 21 publications
3
44
0
Order By: Relevance
“…Some authors suggest that exhausting all pharmacological options before considering DBS can delay the surgery to a time when the patient is no longer fit because of disease progression [58,127,128]. …”
Section: Timing Of the Surgerymentioning
confidence: 99%
“…Some authors suggest that exhausting all pharmacological options before considering DBS can delay the surgery to a time when the patient is no longer fit because of disease progression [58,127,128]. …”
Section: Timing Of the Surgerymentioning
confidence: 99%
“…Age was probably the major contributor and risk factor for the intracranial bleeding, postoperative confusion, and later dementia development [26, 40, 41]. …”
Section: Discussionmentioning
confidence: 99%
“…The study found a significant correlation between the FLASQ-PD scores recorded and the ultimate decision of the DBS interdisciplinary team [41]. In another study, Moro et al [42] used the RAND method to evaluate surgical candidacy. In their study, the authors examined 972 patient profiles, and observed that the appropriateness for surgical referral was correct in 33 % of the patients.…”
Section: Florida Surgical Questionnaire-pd and Rand Methods For Screementioning
confidence: 98%